(untitled) (Research, Society and Development, 2021)
This is an integrative literature review, whose theme is the complications faced by diabetic patients in the healing process: a pharmaceutical approach. This literature review used data from the Medical Literature Analysis and Retrieval System online (Medline), the Scientific Electronic Library Online (Scielo), Latin American and Caribbean Health Sciences Literature (LILACS), Google Scholar and data from PUBMED. Diabetes Mellitus has a high incidence in the world population, being a chronic metabolic disease, divided into type 1 and type 2 diabetes, with type 2 diabetes being the most common in the population, which represents a dysfunction in insulin activity (pancreatic hormone), both characterized by elevation of the glycemic level in patients. Such pathological change can bring serious complications to diabetic patients, especially complications in tissue injury repair. The importance of the approach to patients with diabetes mellitus is due to the large index of the population that is diagnosed and/or has a predisposition to develop this metabolic syndrome. The application of appropriate therapies is a major point of attention for the success of therapies, with medicinal plants and their active metabolites being of great value for success in the therapy of lesions in diabetics. Based on this, the various authors described in the study emphasize the therapeutic possibilities, inserted in clinical practice and raise the possibilities of pharmaceutical products that can be used in the treatment of lesions in diabetics. Finally, we conclude that it is extremely important to continue studies for a better understanding of the subject in order to minimize complications associated with healing in diabetics.